Implementation of an guided inquiry learning model in the reaction rate theory to improve the student creative thinking skills - Nirmala Delawanti; Achmad Lutfi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to analyze the implementation of guided inquiry learning, student activities, students' creative thinking skills, and student responses after the guided inquiry model implementation on the reaction rate theory. The investigation uses a quantitative descriptive method with a one-group pretest-posttest design. The data collection method used the observation method, and the tests were tested using the normality test, Paired Sample T-Test, and n-gain. The subjects of this study were the eleventh-grade student at SMAN 7 Kediri, East Java, Indonesia. It shows that guided inquiry learning to improve creative thinking skills has been carried out well. Students use 16% of the time at meeting 1 and 15% at meeting 2 to practice fluency. 23% and 26% at meetings 1 and 2 to practice flexibility, and 11% of meeting time 1 and 8% of meeting 2 is used to practice elaboration. The students' creative thinking skills increased from before and after applying guided inquiry. There were 8 students categorized as quite creative and 24 others less creative before the learning was carried out. After learning, as many as 11 students were categorized as creative, and 21 others were very creative.